Effects of agritourism development on the local community in Kericho County, Kenya - Nicholas Kipkorir; Nzomo S. Twili; Adol Gogo (Bahasa Indonesia, 2022)
This paper examines the effects of agritourism development on local communities in Kericho County, Kenya. Descriptive research design was used targeting agritourism stakeholders in Kericho with a sample size of 40 respondents. Questionnaires were used to collect primary data, with the findings indicating that the association between agritourism development and socio-cultural, environmental, and economic impacts was strong and positive. The study also revealed that agritourism had enhanced the local community's dignity and value, leading to new social recognition as a leading tea zone nationally and internationally. The study concludes that notable negative social impact is acquiring new destructive lifestyles such as drug abuse and sexual assaults as agritourists introduce new behaviors, tastes, and preferences. Environmentally, agritourism has aggravated human-wildlife conflicts by constructing tourist infrastructural facilities in the neighboring forest environment. Economically, agritourism has led to the reduction of poverty levels through the creation of employment. The study implies that local stakeholders ought to increase participation through education campaigns to minimize the tribulations associated with agritourism. These findings are invaluable to agritourism stakeholders in developing agritourism policy for Kericho County by incorporating a holistic approach that ensures sustainable agritourism growth.